First measurements of capture reactions for the γ-process using HECTOR. (August 2019) - Simon, A; Kelmar, R; Olivas-Gomez, O; Churchman, E; Millican, P; Reingold, C S; Anderson, T; Clark, A M; Cooper, N; Dombos, A C; Frentz, B; Henderson, S L; et al.
Abstract: The first measurements of the capture reactions for the astrophysical γ-process using HECTOR, a total absorption spectrometer are presented. Two reactions: 102 Pd(p, γ) 103 Ag and 90 Zr(α, γ) 94 Mo were measured using the γ-summing technique. The results are compared with the previous measurements found in the literature and with the NON-SMOKER predictions. The results from the current work are in a good agreement with the data found in the literature and serve as a test of the newly developed detector.